Development of an Expert System for Early Detection of Heart Disease Using The Bayes Theorem Method - Fristi Riandari; Ritha Zahara Tarigan (Jurnal Mantik, 2020)
Coronary heart disease (CHD) is the leading cause of death and disability in developed and developing countries. In 2014 it was also reported that coronary heart disease is one of the causes of death for both men and women, starting in the 25-29 age group and increasing with age. The highest prevalence of coronary heart disease as a cause of death in the 60-64 year age group and in the 70-74 year age group. The development of science and technology has made information technology usable in various fields including health. So it is hoped that by making an application that can make it easier for users to detect heart disease early and independently. The purpose of this study is to build an application by implementing an expert system using the website-based Bayes Theorem method as a tool for diagnosing heart disease. This application was built using the web programming language & MySQL database. Expert system application to help detect heart disease early.